Capoeira sou eu: trajetórias de uma capoeirista e sua formação acadêmica na dança - BAÍA, Carla Suellen Castro (2021)
Capoeira one of the elements of greater representativity of struggle and resistance of our ancestors, inheritance of the African peoples, appears here as fundamental base in the construction of my dance. This research has as a guiding objective to analyze the contribution of capoeira in my training in dance, more specifically in the academic scope of the Degree in Dance. Based on my experiences from the Technical Course in Interpreter - creator in Dance of the UFPA to the Degree in Dance - UFPA, starting from the affirmation that capoeira was a fundamental element for the construction of a body that dances, contributing with its works of rhythm , historical context, vocabulary of movement and philosophy of life. The present research presents a qualitative autobiographical approach, using as main theorists Vianna (2008), Miller (2007), Strazzacappa (2012) and Bolsanello (2011) on the studies of Somatic Education to understand the body related to dance and my experience in capoeira that to acquire during the studies in the graduation in dance, then comes the understanding of the Body in Alertness that comes loaded of memory of its experiences in the capoeira and that when having contact with the dance and its concepts, manages to perceive the potency of its practices as body who dances. From this result came the choreographic study entitled Berimbolar: tapping in the rhythm of capoeira, which brought to the scene all the elements of capoeira, worked on the look of the North American tap dance.